Issue of historical and cultural capacity and possibility of its exploitation for cultural tourism in Altai Republic - Takarakova, Evgenia O. (The New Research of Tuva, 2013)
Article considers the historical and cultural capacity of the Altai Republic as a basis for development of ecological and cultural tourism in the region. The main objects and the factors influencing its development are revealed.